ANALYSIS REACTIVITY OF PUNICA GRANATUM POLYPHENOLS TO THE OSTEOCALCIN, BONE MORPHOGENETIC PROTEIN-2, AND COLLAGEN TYPE-1 - Burhan, Edrizal; Thahar, Bergman; Abidin, Trimurni; Putra, Deddi Prima; Gani, Basri A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Punica granatum (PG) contains anthocyanins which are useful as antioxidants, anti-inflammatory, and prevent cancer, while also increasing bone cell proliferation and osteoblasts differentiation in bone remodeling. Methods: The reactivity of osteocalcin protein markers with PG polyphenol fractionation hydrogels observed using enzyme-linked immunosorbent assay, the degree of reactivity was determined by optical density at 550 nm. Results: PG butanol fraction has better reactivity compared to the total extract, ethyl, and hexane fraction. Based on the reactivity distribution, bone morphogenetic protein (BMP)-2 and collagen Type-1 had a dominant distribution compared to osteocalcin, but the theses proteins had a strong relation (r = 0.8) with probability (P < 0.05). Conclusion: PG butanol fraction had better reactivity to osteocalcin, BMP-2, and collagen Type-1 compared with total extract, hexane, and ethyl fraction. The four PG polyphenol fractionations have dominant reactivity to BMP-2.